2020
DOI: 10.1016/j.ijid.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-invasive/invasive ventilatory support in patients with COVID-19 pneumonia: A retrospective study within a multidisciplinary approach

Abstract: To investigate risk factors for non-invasive/invasive ventilatory support (NI/I-VS) in patients with coronavirus disease 2019 (COVID-19). Methods: All consecutive patients admitted to the Infectious Diseases Unit and Intensive Care Unit (ICU) of Santa Maria Annunziata Hospital (Florence, Italy), from February 25 to April 25, 2020, with a confirmed COVID-19 diagnosis were enrolled in this retrospective cohort study. NI/I-VS was defined as the need for continuous positive airway pressure (CPAP) or bilevel positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…Search terms yielded 84 articles relating to a total of 13 140 patients after exclusion of duplicates, and after screening titles, abstracts, and full text for relevance specifically to outcomes with the use of NIRS in patients with COVID-19 ( appendix p 1 ). 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Search terms yielded 84 articles relating to a total of 13 140 patients after exclusion of duplicates, and after screening titles, abstracts, and full text for relevance specifically to outcomes with the use of NIRS in patients with COVID-19 ( appendix p 1 ). 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
“…Other than two multicentre RCTs from Italy and the UK, 38 , 95 22 prospective and 61 retrospective observational studies were identified, reporting a median of 71 patients (IQR 40–127) per study. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Data selection was based on a previous work of this group about risk factors for severe illness in COVID-19 patients. 2 In the patients' group, we compared median HR during RDV administration with the median HR of the 3 days before RDV administration and the median HR of the 3 days after RDV administration. Moreover, we compared incidence of bradycardia between patients and controls.…”
mentioning
confidence: 99%
“…The pace of disease progression is variable but previous studies indicate that clinical deterioration typically occurs approximately five to seven days after symptom onset [12]. Predicting exactly which patients are most likely to require mechanical ventilation or die has been an area of active research [8][9][10][11][12][13]. To this end, multiple predictive scoring systems have been developed to assist clinicians in identifying such patients [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%